Bacillus subtilis comes of age as a vaccine production host and delivery vehicle. (August 2015) - Rosales-Mendoza, Sergio; Angulo, Carlos
<x xml:space="preserve">Abstract</x> Bacillus subtilis is a vaccine production host and delivery vector with several advantages such as a low production cost, straightforward administration as it is safe for human consumption and the production of spores exerting adjuvant effects. This review summarizes the expression approaches and provides an updated outlook of how a myriad of pathogens have been targeted under this technology. Furthermore, by reviewing the literature, several promising candidates in terms of immunogenic and immunoprotective potential have been identified. The immune profiles achieved comprise either humoral or cellular responses, which reflect versatility for application in the fight of distinct pathologies that demand specific polarization on the immune responses. Some perspectives for this field are also envisioned.